The battle for coal : miners and the politics of nationalization in France ; 1940 - 1950 - Holter, Darryl (Northern Illinois Univ. Press, 1992)
As World War II came to a close, economic recovery in France hinged on coal. With nearly 90 percent of French energy dependent on coal and imported coal unavailable, France, traditionally the world's largest importer, was forced to rely on its own troubled coal-mining industry. The Battle for Coal is the first full study to address the history and politics of coal production in post-World War II France. Holter examines the French coal-mining industry's role in postwar reconstruction and the state's intervention into the industry in an effort to promote economic expansion. He traces the complex "battle for coal" that took place as government officials, labor leaders, management personnel, and mine workers struggled to increase production while transforming a private industry into a state-owned one. After surveying French coal-mining to 1939, Holter analyzes the impact of nationalization on production, the effects of the cold war on coal politics, and the coal strikes that rocked France in 1947 and 1948. Holter locates French industrial policy in the context of nationalization, national and local politics, and more broadly the emerging cold-war economy of postwar Europe, showing how the "battle for coal" related to the movement toward European economic integration. He focuses primarily on the role of labor in the process of nationalization. His insights into labor relations and the successes and limitations of a union-led production campaign provide a new understanding of the paradoxical nature of state-owned industries.